Theoretical Aspects Of Ecological Intelligence Development Of Students In Elementary Schools - Zulfikar, Hari Ahmad; Supriatna, Nana; Nurbaeti, Iyus (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The environment is defined as a place where living things carry out their life activities. Clean and sustainable environment can sustain continuous life(sustainability).Therefore, intelligence is needed to support it, one of the intelligence that is the basis for this ecological intelligence (ecoliteracy). Every behavior or action of a person based on ecological intelligence,it does not only have an impact on himself and others, but also on other living things and the nature around where a person lives or in other terms